Rencana Reklamasi pada Penambangan Batu Gamping PT.Z - Andrawina Andrawina (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
This study examines the reclamation plan of PT. Z for the 2023–2027 period with the aim of assessing the technical feasibility, ecological effectiveness, and alignment with national reclamation regulations. A descriptive-quantitative approach was employed through field observations, analysis of geomorphological conditions, evaluation of topsoil management, assessment of revegetation performance, and review of key environmental documents. The planned land disturbance reaches 138.53 ha, with reclamation focused on the disposal and topsoil areas covering 29.67 ha, as the mining pit remains active. Reclamation activities include land recontouring, topsoil spreading, erosion control, establishment of Legume Cover Crops (LCC), and planting of local species such as Rukam. The results indicate that the implemented strategies effectively enhance soil stability, improve vegetation cover, and support ecosystem recovery. Furthermore, the reclamation program meets the key performance criteria set by the Ministry of Energy and Mineral Resources, with vegetation cover exceeding 90% and stable slope conditions. Challenges remain, particularly related to sedimentation management and the absence of pit reclamation during the active mining phase. Overall, the study concludes that PT. Z has developed and executed a reclamation plan that reflects good mining practices and environmental stewardship, contributing to the long-term sustainability of post-mining land use.